2019
DOI: 10.1111/jop.12909
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, attitudes and factors that influence prescribing by general dentists in Australia: A qualitative study

Abstract: Background Longitudinal studies of dental prescribing in Australia show that dentists make some inappropriate prescribing choices; literature has shown that dentists tend to overprescribe antibiotics and prescribe for incorrect indications. The unnecessary use of antibiotics is a contributing factor towards the development of antibiotic resistance. The aims of the study were to obtain a greater understanding of the perceptions, attitudes and factors that influence dental prescribing for all major relevant drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…Unnecessary dental antibiotic prescribing is a complex behaviour which is influenced by a plethora of clinical and non-clinical factors which affect dentists and patients. 21,22 Early in the COVID-19 pandemic, a selection of potential factors driving the increase in dental antibiotic use were identified in a letter to the British Dental Journal editor-in-chief. 2 Access and other systems/process issues were hypothesised as key, noting in particular that some urgent dental centres had been requiring patients to have tried antibiotics before accepting referral for face-to-face care.…”
Section: Discussionmentioning
confidence: 99%
“…Unnecessary dental antibiotic prescribing is a complex behaviour which is influenced by a plethora of clinical and non-clinical factors which affect dentists and patients. 21,22 Early in the COVID-19 pandemic, a selection of potential factors driving the increase in dental antibiotic use were identified in a letter to the British Dental Journal editor-in-chief. 2 Access and other systems/process issues were hypothesised as key, noting in particular that some urgent dental centres had been requiring patients to have tried antibiotics before accepting referral for face-to-face care.…”
Section: Discussionmentioning
confidence: 99%
“…About one in four dentists in Australia (16-27%) would preference the use of analgesics only (paracetamol, paracetamol/ codeine, tramadol or oxycodone) for dental pain, instead of NSAIDs 29 . Australian dentists tend to recommend tramadol if their patient is allergic or finds codeine ineffective 30 , despite both medicines requiring transformation by cytochrome P450 2D6 to the active metabolites. The pharmacogenomic variability of cytochrome P450 2D6 is well established and therefore patients who have inherited two non-functional alleles of this enzyme will likely find both medicines ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacogenomic variability of cytochrome P450 2D6 is well established and therefore patients who have inherited two non-functional alleles of this enzyme will likely find both medicines ineffective. In addition, other non-clinical factors have been identified for prescribing by Australian dentists, such as patient pressure, fear of litigation, and the desire by dentists to make patients feel well managed 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study on perceptions and reasons for prescribing antibiotics for therapeutic uses revealed that for conditions such as irreversible pulpitis, localised odontogenic infections and alveolar osteitis where antibiotics are not warranted, dentists tended to prescribe antibiotics based on the severity of the patient’s symptoms, rather than clinical signs. [32] The study also revealed that there was a strong desire by dentists to give distressed patients who were in pain the impression that the dentist was doing everything possible to resolve their symptoms so patients would consequently feel that they were well managed, and the prescribing of antibiotics was one such method. [32]…”
Section: Discussionmentioning
confidence: 99%